2022
DOI: 10.3390/d14040249
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Seasonal Patterns of Calling Activity of Seven Cuculidae Species in a Forest of Eastern China

Abstract: There is very little information on the diurnal and seasonal patterns of Cuculidae species’ calling activity in subtropical areas. In this study, we used passive acoustic monitoring to investigate the diurnal and seasonal patterns of calling activity of seven Cuculidae species at three sites in eastern China’s forest over a year. Our results showed that these species exhibited significant diurnal variations except for Cuculus micropterus. Eudynamys scolopaceus and Cuculus saturatus increased their vocal activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 79 publications
(115 reference statements)
0
12
0
1
Order By: Relevance
“…Although songs of Asian Koel and Indian Cuckoo have similar frequencies and daily temporal distribution, they do not overlap in acoustic niche space. Large Hawk-Cuckoo and Lesser Cuckoo were separated in seasonal distribution (Mei et al 2022). We suggest that the seven species may have flexible mechanisms to partition their acoustic niche in multiple dimensions (Chitnis et al 2020).…”
Section: Relationship Between Spectral Distribution and Temporal Dist...mentioning
confidence: 82%
See 2 more Smart Citations
“…Although songs of Asian Koel and Indian Cuckoo have similar frequencies and daily temporal distribution, they do not overlap in acoustic niche space. Large Hawk-Cuckoo and Lesser Cuckoo were separated in seasonal distribution (Mei et al 2022). We suggest that the seven species may have flexible mechanisms to partition their acoustic niche in multiple dimensions (Chitnis et al 2020).…”
Section: Relationship Between Spectral Distribution and Temporal Dist...mentioning
confidence: 82%
“…Finally, Chesnut-winged Cuckoo gives a harsh metallic 'koo-ree' call . See Figure S2 and Mei et al (2022) for spectral characteristics of typical calls of these species. Some of these species have different call types (Huang et al 2017) or female and male individuals have different calls (Yoo et al 2020), and in our study we only considered male cuckoos' calls or the most common call type because males typically call much more frequently than females (Yoo et al 2020) and the vocal activity of females has little effect on overlap.…”
Section: Calling Activity Of Target Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…lluvias, temperatura, humedad), el establecimiento de territorios para atraer parejas, para localizar alimento o alertar sobre la presencia de posibles depredadores (Keast 1994;La 2012;Voigt et al, 2021). Las especies de aves diurnas vocalizan mayormente al amanecer y al atardecer, cuando los niveles de luz solar son bajos; como así también, debido a que las bajas temperaturas en estos momentos del día hacen más efectiva la transmisión del sonido (Clark 2012;Mei et al, 2022). Mientras que las lluvias de mediana o fuerte intensidad pueden reducir la actividad vocal, debido a la interferencia acústica que provoca el ruido producido por las gotas de agua al caer sobre la vegetación (Vokurková et al, 2018).…”
Section: Introductionunclassified
“…Another study from China conducted an inter-species comparison of the calling activity of seven Cuculidae species that use nesting parasitism [3]. The authors clearly showed that both diurnal and temporal patterns of the calling activities differed among the species.…”
mentioning
confidence: 99%